Guinea Pig Herpes-Like Virus Infections II. Antibody Response and Virus Persistence in Mice and Rabbits - Lam, K. M. (1973)
Mice inoculated with guinea pig herpes-like virus produced minimal, if any, antibody response, and no virus was isolated from the inoculated animals 64 days after administration. The antibody response in rabbits inoculated with the same virus was prompt and reached a high level within 14 to 29 days regardless of the site of inoculation. Long-term persistence of viremia was observed only in intravenously inoculated rabbits; a brief period of viremia was observed in intraperitoneally inoculated rabbits, but no viremia was obtained in rabbits inoculated by the subcutaneous route. Maternal antibody was transferred readily to offspring; however, transference of infectious virus from mother to offspring was demonstrable in only one of 75 fetuses tested.